PEDAGOGICAL AGENTS FOR STUDENTS WITH AUTISM: A CONTEMPORARY WORLDWIDE BIBLIOMETRIC INSIGHT - Nawi, Nur Syifaa Mohd; Hamzah, Mahizer; Rokeman, Muhammad Ihsan (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This bibliometric study examines the development of research on pedagogical agents for students with autism, a field that has gained increasing attention as digital learning tools become more sophisticated and widely used in special education. This field of research has seen an ever-increasing interest with educators and researchers examining the ways in which virtual tutors, conversational agents, and avatars may be used as cognitive, social, and behavioural learning aids with autistic learners. The research is timely in response to the demand to know the world trends, contributions of various disciplines, powerful nations, and prevailing research areas and patterns of cooperation that inform this field. Data were collected using Scopus advanced search, producing a final dataset of 219 publications that met the established criteria. OpenRefine was used to clean up and normalise the dataset by eliminating duplicate data and merging conflicting records. The Scopus Analyzer was used to study statistical trends, an increase in publications and distribution of subjects, where co-occurrence networks, keyword clusters and co-authorship structures were drawn up with the help of VOSviewer. The numerical findings show consistent publication growth across the last decade, with computer science emerging as the primary disciplinary contributor, followed by medicine, engineering, social sciences, and psychology. The United States, China, Italy, the United Kingdom, France, and Japan appear as the most productive countries, forming strong collaboration networks. Keywords such as autism, virtual reality, avatar, augmented reality, conversational agent, eye-tracking, and human-computer interaction dominate the research landscape, revealing a strong emphasis on immersive technologies and behavioural analysis. The results highlight a field that has evolved into a multidisciplinary space where advanced digital technologies intersect with educational and clinical needs. On the whole, the study offers a very broad overview of the way pedagogical agents are currently being researched throughout the world and highlights the fact that AI-enhanced tools are becoming more and more relevant to the learning process of autistic students, as well as their communication and engagement in the digital world.